PERAN CITRA MEREK DALAM MEMEDIASI PENGARUH WORD OF MOUTH TERHADAP NIAT BELI SEPEDA MOTOR YAMAHA NMAX DI KOTA DENPASAR - Prayoga, I Putu Agus Sipta; Warmika, I Gede Ketut (E-Jurnal Manajemen; Vol 8 No 2 (2019), 2019)
The purpose of this study was to explain the effect of word of mouth (WOM) and brand image on the purchase intention of Yamaha Nmax motorbikes in Denpasar City, to explain the influence of word of mouth (WOM) on the brand image of Yamaha Nmax motorbikes in Denpasar City, and to explain the role of brand image as a variable mediating the influence of word of mouth (WOM) on the intention to buy Yamaha Nmax motorbikes in Denpasar City. The population in this study were prospective consumers of Yamaha Nmax Motorcycles living in Denpasar City. The sample determination technique used in this study is purposive sampling, which is the technique of determining the sample by considering certain criteria. The number of respondents samples taken is determined at least 5-10 times the number of indicators as many as 12, so the sample used in this study amounted to 120 respondents. The data analysis technique used in this research is Path Analysis. The results showed that Word of mouth had a positive and significant effect on purchase intention, Word of mouth had a positive and significant effect on brand image, brand image had a positive and significant effect on purchase intention, and brand image positively and significantly mediated the influence of word of mouth on intention buy on Yamaha Nmax motorcycle products. Keywords: word of mouth (WOM), brand image, purchase intention